2018
DOI: 10.15171/jrip.2019.19
|View full text |Cite
|
Sign up to set email alerts
|

Comparison the effect of high flux and low flux dialyzer on quality of life in hemodialysis patients; a clinical trial

Abstract: Introduction: End-stage renal disease (ESRD) is a worldwide public health problem. ESRD reduces health-related quality of life. Quality of life is an important determinant in the mortality and morbidity of hemodialysis patients. However, several studies have suggested that high flux dialyzers increase dialysis adequacy and reduce mortality and morbidity in these patients. Objectives: This study aimed to investigate the effects of high flux and low flux dialyzers on the quality of life in hemodialysis patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…12 Oshvandi et alalso demonstrated that high flux dialyzers improved the quality of life of patients as compared to low flux dialyzers. 13 Our study associated high-flux membranes with greater protein loss than low-flux membranes. Our results are in contrast to observations made previously.…”
Section: Discussionmentioning
confidence: 65%
“…12 Oshvandi et alalso demonstrated that high flux dialyzers improved the quality of life of patients as compared to low flux dialyzers. 13 Our study associated high-flux membranes with greater protein loss than low-flux membranes. Our results are in contrast to observations made previously.…”
Section: Discussionmentioning
confidence: 65%